Recruitment of Lyn from endomembranes to the plasma membrane through calcium-dependent cell-cell interactions upon polarization of inducible Lyn-expressing MDCK cells - Takao Morinaga (Nature Portfolio, 2017)
Abstract Src-family kinases, expressed in a wide variety of cell types, are anchored to cellular membranes through posttranslational lipid modifications and involved in diverse cellular signalling. In epithelial cells, Src-family kinases are localized at the plasma membrane and participate in epithelial functions. Epithelial cell polarity is achieved through dynamic reorganization of protein trafficking. To examine the trafficking of Src-family kinases between polarized and non-polarized epithelial cells, we generated an MDCK cell line that can inducibly express a protein of interest in a polarized state at any time. We show here that Lyn, a member of Src-family kinases, mainly localizes to the plasma membrane in polarized MDCK cells and to endomembranes in non-polarized MDCK cells. Cell-cell interactions between adjacent MDCK cells recruit Lyn from endomembranes to the plasma membrane even without cell attachment to extracellular matrix scaffolds, and loss of cell-cell interactions by calcium deprivation relocates Lyn from the plasma membrane to endomembranes through Rab11-mediated recycling. Therefore, using our MDCK cells expressing inducible Lyn, we reveal that calcium-dependent cell-cell interactions play a critical role in plasma membrane localization of Lyn in polarized MDCK cells.